1998
DOI: 10.1152/ajprenal.1998.275.3.f433
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HKα2protein is increased selectively in renal medulla by chronic hypokalemia

Abstract: Our laboratory has demonstrated by Northern analysis that chronic hypokalemia increases HKα2 (i.e., α-subunit of the colonic H+-K+-ATPase) mRNA abundance in the rat. To determine whether the increase in mRNA correlated with an increase in HKα2 protein, an antibody was raised against a synthetic peptide derived from amino acids 686–698 of the HKα2sequence. The anti-HKα2 antibody hybridized to rat distal colon membranes which migrated at ∼100 kDa (expected mobility of HKα2). HKα2 protein was not detected in plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 22 publications
1
42
1
Order By: Relevance
“…As expected, overall Na ϩ balance in- The effect of long-term mineralocorticoid excess to change H ϩ ,K ϩ -ATPase activity and its relation to dietary K ϩ intake has previously been examined by Eiam-Ong et al 11 In contrast to the results described here, 7-day exposure to low, normal, or high aldosterone levels in rats fed diets consisting of low, normal, and high K ϩ content did not significantly affect Schering 28080 -sensitive (a gastric or HK␣ 1 -containing H The renal H ϩ ,K ϩ -ATPases have been purported to act as primarily K ϩ reabsorptive mechanisms. Because hypokalemia has been shown to substantially increase medullary HK␣ 2 expression [17][18][19] and hypokalemia was quite evident with DOCP treatment, the induction of HK␣ 2 expression in the outer and inner medulla of DOCP-treated mice could be a result of hypokalemia. Abolishment of DOCP-induced HK␣ 2 mRNA expression in the medulla by high K ϩ is consistent with this hypothesis.…”
Section: Docp Induced Medullary Hk␣ 2 Mrna Expressionmentioning
confidence: 99%
“…As expected, overall Na ϩ balance in- The effect of long-term mineralocorticoid excess to change H ϩ ,K ϩ -ATPase activity and its relation to dietary K ϩ intake has previously been examined by Eiam-Ong et al 11 In contrast to the results described here, 7-day exposure to low, normal, or high aldosterone levels in rats fed diets consisting of low, normal, and high K ϩ content did not significantly affect Schering 28080 -sensitive (a gastric or HK␣ 1 -containing H The renal H ϩ ,K ϩ -ATPases have been purported to act as primarily K ϩ reabsorptive mechanisms. Because hypokalemia has been shown to substantially increase medullary HK␣ 2 expression [17][18][19] and hypokalemia was quite evident with DOCP treatment, the induction of HK␣ 2 expression in the outer and inner medulla of DOCP-treated mice could be a result of hypokalemia. Abolishment of DOCP-induced HK␣ 2 mRNA expression in the medulla by high K ϩ is consistent with this hypothesis.…”
Section: Docp Induced Medullary Hk␣ 2 Mrna Expressionmentioning
confidence: 99%
“…Before immunostaining, all tissues were microwaved with 10 mM sodium citrate pH 6.0 or 50 mM Tris-HCl pH 10.0 for 5 minutes at 90°C at a maximum power of 1150 W. Twenty minutes after treatment, sections were washed with three changes of 50 mM Tris-HCl pH 7.8 and then incubated overnight with various dilutions of the following antibodies: (1) an anti-peptide antibody directed to residues 888-906 of rat ClC-2 (1:100 to 1:500). This antibody recognizes the C-terminus epitope RSRHGLPREGTPSDSDDKC of rat ClC-2 that is identical in the mouse molecule (ACL-002, Alomone Labs, Jerusalem, Israel); (2) an antibody to NKCC1 (Kurihara et al, 1999) (1:1000 to 1:5000), kindly provided by R. James Turner; or (3) an antibody to ␣2 subunit of H + /K + ATPase (Codina et al, 1998) (1:1000 to 1:2500), kindly given by Juan Codina. Anti-ClC-2 antibodies initially tested also included sc-16429 and sc-16430 (Santa Cruz Biotechnology, Santa Cruz CA, USA, 1:100 to 1:2000 dilutions).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…HEK-293 cells were transfected with rat HK␣2 in pcDNA3.1(ϩ)-Neo and rat NK␤1 in pcDNA3.1(ϩ)-Zeo (8, 23) using the Lipofectamine PLUS method (10, 11) and selected with 250 g/ml of G418 and 250 g/ml zeocin. Individual colonies were isolated and tested for expression of HK␣2 and NK␤1 by immunoblot analysis (7). Human GPR4 (pcDNA3GPR4) was transiently transfected into HEK-293 cells stably expressing HK␣2/NK␤1.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, HK␣ 2 appears to be upregulated in rodent kidney in response to a number of other stimuli, including metabolic acidosis (37,43,44), respiratory acidosis (16), chronic metabolic alkalosis (with hypokalemia) (15), development of the newborn (9, 12), and potassium depletion (1,7,20). Expression and functionality of proton transporters in different experimental models, including HK␣ 2 , have been attributed to both transcriptional and posttranscriptional events (2,6,11,14,24,45 (27) and Radu et al (35) demonstrated that GPR4 expressed in HEK-293 cells induces accumulation of intracellular cAMP when the cells are challenged with a low extracellular pH.…”
mentioning
confidence: 99%